East African highland bananas (Musa spp. AAAEA) worry more about potassium deficiency than drought stress - Taulya, Godfrey (Elsevier, 2013)
Drought stress, potassium (K) and nitrogen (N) deficiencies are major constraints to rain-fed East African highland banana (EAHB) production in Uganda. It was hypothesised that the reduction in fresh bunch mass and increase in dry matter (DM) allocation to corms with drought stress, K and N deficiency is additive. Individual plant measurements at harvest from two field trials in central and south western Uganda were analyzed to evaluate effects of cumulative rainfall (CRF) received 365 days from sucker emergence, mineral K and N inputs on EAHB bunch yields. Dry matter content in aerial shoot (leaves and pseudostems) relative to that in the subterranean corm was also analyzed to evaluate DM allocation plasticity due to drought stress, K and N deficiency. This was verified with allometric analysis using pre-harvest stage plants from farms of known K and N nutritional status and plants from a screen house drought stress pot trial in Uganda. Dry matter production and yields were mainly driven by K interacting with CRF. Within 12 months, K input (250–600 kg K ha−1 yr−1) increased bunch yield from 8 to 15 Mg ha−1 yr−1 irrespective of whether dry (CRF < 1100 mm) or wet (CRF ≥ 1100 mm) conditions prevailed, possibly due to K-mediated osmotic adjustment under dry conditions. Without K input, wet conditions increased bunch yield from 6 to 8 Mg ha−1 yr−1 while dry conditions decreased it from 6 to 4 Mg ha−1 yr−1 within 12 months. Total DM and its distribution between the biomass structures followed similar trends. Nitrogen input (150–400 kg N ha−1 yr−1) neither affected bunch yield nor DM allocation at harvest stage. At pre-harvest stage, reduction in DM allocation to the corm per unit increase in total DM was 14–22% significantly lower with N and/or K deficiency compared with that under sufficient K and N. Drought stress per se had no effect on DM allocation but enhanced DM allocation shifts due to K deficiency. Drought-stressed EAHB thus increase DM allocation to subterranean structures only if K-deficient, unlike responses reported for other plant species. Potassium nutrition is perhaps a more viable entry point for mitigation of drought stress in EAHB cropping systems than irrigation but this requires further agronomic and economic evaluation. It may be important to account for carbon allocated to osmotic adjustment for realistic simulation of water- and K-limited growth in EAHB.